Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) 3A=1.2.3 + 2.3.3 + 3.4.3 +... + n.(n+1).3
=1.2.(3-0) + 2.3.(4-1) + ... + n.(n+1).[(n+2)-(n-1)]
=[1.2.3+ 2.3.4 + ...+ (n-1).n.(n+1)+ n.(n+1)(n+2)] - [0.1.2+ 1.2.3 +...+(n-1).n.(n+1)]
=n.(n+1).(n+2)
=>S=[n.(n+1).(n+2)] : 3
S = 1 + 3 + 32 + 33 + ... + 330
3S = 3 + 32 + 33 + 34 + ... + 331
3S - S = ( 3 + 32 + 33 + 34 + ... + 331 ) - ( 1 + 3 + 32 + 33 + ... + 330 )
2S = 331 - 1
S = \(\frac{3^{31}-1}{2}\)
\(S=1+3+3^2+3^3+...+3^{30}\)
\(S=1+3\left(1+3^2+...+3^{29}\right)\)
\(S=1+3\left(S-3^{30}\right)\)
\(S=1+3S-3^{31}\)
\(2S=3^{31}-1\)
\(S=\frac{3^{31}-1}{2}\)
\(N=1+4+4^2+...+4^{132}=1+4\left(1+4^2+...+4^{131}\right)\)
\(N=1+3\left(N-4^{132}\right)\)
\(N=1+3N-4^{133}=\frac{4^{133}-1}{2}\)
A=(1/1.2.3-1/2.3.4)+(1/2.3.4-1/3.4.5)+..............+(1/n(n+1)(n+2)-1/(n+1)(n+2)(n+3))
A=1/1.2.3-1/(n+1)(n+2)(n+3)
A=1/18-1/(n+1)(n+2)(n+3)
đúng nhé
Ta có:
A=2+2^2+2^3+2^4+.....+2^100
=> 2A=2^2+2^3+...+2^101
=> 2A-A=A=(2^2+2^3+...+2^101)-(2+2^2+2^3+2^4.....+2^100)
=> A=2^2+2^3+...+2^101-2-2^2-...-2^100
=> A=2^101-2
B=1+3+3^2+3^2+....+3^2009
=> 3B=3+3^2+3^2+....+3^2010
=> 3B-B=2B=3+3^2+3^2....+3^2010-1-3-3^2-3^2-....-3^2009
=> 2B=3^2010-1
=> B=(3^2010-1)/2
C=1+5+5^2+5^3+...+5^1998
=> 5C=5+5^2+5^3+...+5^1999
=> 5C-C=4C=5+5^2+5^3+...+5^1999-1-5-5^2-5^3-...-5^1998
=> 4C=5^1999-1
=> C=(5^1999-1)/4
D=4+4^2+4^3+...+4^n
=> 4D=4^2+4^3+...+4^n+1
=> 4D-D=3D=4^2+4^3+...+4^n+1 - 4-4^2-4^3-...-4^n
=> 3D=4^n+1 - 4
=> 3D=\(\frac{4^{n+1}-4}{3}\)
Ta có : \(A=2+2^2+2^3+.....+2^{100}\)
\(2A=2+2^2+2^3+.....+2^{101}\)
\(2A-A=2^{101}-2\)
\(A=2^{101}-2\)
a)A=1+2+22+...+21000
2A=2(1+2+22+...+21000)
2A=2+22+...+21001
2A-A=(2+22+...+21001)-(1+2+22+...+21000)
A=21001-1
b)B=3+32+...+32015
3B=3(3+32+...+32015)
3B=32+33+...+32016
3B-B=(32+33+...+32016)-(3+32+...+32015)
2B=22016-3
\(B=\frac{2^{2016}-3}{2}\)
c)C=4+42+...+4n
4C=4(4+42+...+4n)
4C=42+43+...+4n+1
4C-C=(42+43+...+4n+1)-(4+42+...+4n)
3C=4n+1-4
\(C=\frac{4^{n+1}-4}{3}\)
Ta có: A = 1 + 2 + 22 + ...... + 2100
=> 2A = 2 + 22 + 23 + ...... + 2101
=> 2A - A = 2101 - 1
=> A = 2101 - 1
B = 3 + 32 + 33 + ...... + 22015
=> 3B = 32 + 33 + 34 + ...... + 22016
=> 3B - B = 32016 - 3
=> 2B = 32016 - 3
=> B = 32016 - 3/2
C = 4 + 42 + 43 + .... + 4n
=> 4C = 42 + 43 + 44 + ..... + 4n + 1
=> 4C - C = 4n + 1 - 4
=> 3C = 4n + 1 - 4
=> C = 4n + 1 - 4 / 3